2012
DOI: 10.1002/jbm.a.34041
|View full text |Cite
|
Sign up to set email alerts
|

The application of tissue engineering in reversing mitomycin C‐induced ischemic conjunctiva

Abstract: The purpose of this study is to evaluate the angiogenic potential of collagen-glycosaminoglycan (CG) matrices in mitomycin C-induced ischemic conjunctival defect, in New Zealand white rabbits. After creating a conjunctival defect at the center of ischemic conjunctiva, a CG matrix was implanted into subconjunctival space to evaluate the conjunctival reepithelialization and angiogenesis during the wound healing process. In the grafted group, the vessel count of the healed conjunctiva was substantially elevated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…As CGM implants are also thought to promote angiogenesis and to counteract the ischaemic complications of the antimetabolite mitomycin C following glaucoma surgery,8 secondary implantation of collagen matrix implant in post-trabeculectomy eyes with ocular hypotony should present a useful combined mechanical and biological approach to limiting overfiltration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As CGM implants are also thought to promote angiogenesis and to counteract the ischaemic complications of the antimetabolite mitomycin C following glaucoma surgery,8 secondary implantation of collagen matrix implant in post-trabeculectomy eyes with ocular hypotony should present a useful combined mechanical and biological approach to limiting overfiltration.…”
Section: Discussionmentioning
confidence: 99%
“…An animal study about the treatment of a mitomycin C-altered conjunctiva by CGM use has demonstrated by histology that an inflammatory response around and inside the matrix had taken place at day 7 postoperatively and that the use of the CGM had improved vascularity in a previously avascular area at week 4 8. However, the authors found the time needed for epithelial closure of an experimental wound or attainment of final conjunctival thickness to be independent of whether or not CGM was used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,7,[9][10][11]13,15 For example, Kim 5 used MMC eye drops (0.0002 mg/ml) 4 times daily for 2-5 days after regional conjunctivectomy for chronic conjunctival injection. Conjunctival epithelial defects persisted up to 27 months (mean 13.65 months) after the surgery and produced many complications such as thinning of the sclera or avascular necrosis of the sclera in as many as 92% of the patients.…”
Section: 16mentioning
confidence: 99%
“…In the field of neurooncology, several research studies have already demonstrated the benefits of intraoperative imaging (either with ultrasonography 21 or, more markedly, with high-field intraoperative MRI 1 ) as adjuvant techniques that may provide a more accurate evaluation of the extent of tumoral resection. Similarly, in vascular neurosurgery, the use of intraoperative angiography 11 and, more recently, the developments of indocyanine green videoangiography 10 have also substantially contributed to improving the quality of the neurosurgical procedures for intracranial aneurysms and arteriovenous malformations.…”
mentioning
confidence: 99%